X-men : Dark Phoenix - Turner, Sophie, 1996-; Lawrence, Jennifer, 1990-; McAvoy, James, 1979-; Chastain, Jessica, 1977-; Fassbender, Michael, 1977-; Hoult, Nicholas, 1989-; Peters, Evan, 1987-; Twentieth Century Fox Home Entertainment, Inc. (Beverly Hills, CA : 20th Century Fox Home Entertainment, 2019)
The story of one of the X-Men's most beloved characters, Jean Grey, as she evolves into her iconic alter ego. During a life-threatening rescue mission in space, Jean is hit by a cosmic force that transforms her into one of the most powerful mutants of all. Wrestling with this increasingly unstable power as well as her own personal demons, Jean spirals out of control, tearing the X-Men family apart and threatening to destroy the very fabric of our planet.
Director, Simon Kinberg.
Sophie Turner, Jennifer Lawrence, James Mcavoy, Jessica Chastain, Michael Fassbender, Nicholas Hoult, Evan Peters.
Rating: PG-13; for intense sequences of sci-fi violence and action including some gunplay, disturbing images, and brief strong language.
DVD; NTSC, region 1; wide screen (2.39:1); Dolby digital 5.1 (English), Dolby digital 2.0 stereo (Spanish, French).
English, French or Spanish dialogue; French or Spanish subtitles; English subtitles for the deaf and hard-of-hearing (SDH); English descriptive audio track.
110122
Keywords: X-Men (Fictitious characters) -- Drama; Good and evil -- Drama; Interplanetary voyages -- Drama; Superheroes -- Drama; Feature films; DVD-Video discs; Video recordings for the hearing impaired; Video recordings for people with visual disabilities; Thrillers (Motion pictures); Superhero films; Science fiction films; Film adaptations; Action and adventure films; Drama